Liver-Specific Deletion of Mouse CTCF Leads to Hepatic Steatosis via Augmented PPARγ SignalingSummary - Yeeun Choi (Elsevier, 2021)
Background & Aims: The liver is the major organ for metabolizing lipids, and malfunction of the liver leads to various diseases. Nonalcoholic fatty liver disease is rapidly becoming a major health concern worldwide and is characterized by abnormal retention of excess lipids in the liver. CCCTC-binding factor (CTCF) is a highly conserved zinc finger protein that regulates higher-order chromatin organization and is involved in various gene regulation processes. Here, we sought to determine the physiological role of CTCF in hepatic lipid metabolism. Methods: We generated liver-specific, CTCF-ablated and/or CD36 whole-body knockout mice. Overexpression or knockdown of peroxisome proliferator-activated receptor (PPAR)γ in the liver was achieved using adenovirus. Mice were examined for development of hepatic steatosis and inflammation. RNA sequencing was performed to identify genes affected by CTCF depletion. Genome-wide occupancy of H3K27 acetylation, PPARγ, and CTCF were analyzed by chromatin immunoprecipitation sequencing. Genome-wide chromatin interactions were analyzed by in situ Hi-C. Results: Liver-specific, CTCF-deficient mice developed hepatic steatosis and inflammation when fed a standard chow diet. Global analysis of the transcriptome and enhancer landscape revealed that CTCF-depleted liver showed enhanced accumulation of PPARγ in the nucleus, which leads to increased expression of its downstream target genes, including fat storage-related gene CD36, which is involved in the lipid metabolic process. Hepatic steatosis developed in liver-specific, CTCF-deficient mice was ameliorated by repression of PPARγ via pharmacologic blockade or adenovirus-mediated knockdown, but hardly rescued by additional knockout of CD36. Conclusions: Our data indicate that liver-specific deletion of CTCF leads to hepatosteatosis through augmented PPARγ DNA-binding activity, which up-regulates its downstream target genes associated with the lipid metabolic process.